2020
DOI: 10.1101/2020.11.11.378893
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Glia actively sculpt sensory neurons by controlled phagocytosis to tune animal behavior

Abstract: Glia in the central nervous system engulf neuron fragments during synapse remodeling and recycling of photoreceptor outer-segments. Whether glia passively clear shed neuronal debris, or actively remove neuron fragments is unknown. How pruning of single-neuron endings impacts animal behavior is also unclear. Here we report that adult C. elegans AMsh glia engulf sensory endings of the AFD thermosensory neuron. Engulfment is regulated by temperature, AFD’s sensory input, and tracks AFD activity. Phosphatidylserin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 83 publications
(109 reference statements)
0
3
0
Order By: Relevance
“…Some of these proteins are orthologs of molecules previously implicated in glial engulfment in Drosophila (CED-12/ELMO, CED-10/Rac1 GTPase) and mammalian retina (Rac1 GTPase) (Kevany and Palczewski, 2010;Freeman, 2015) (Table 1). In addition, we uncovered two novel mediators for glial engulfment, including a PS receptor and a regulator of PS exposure (Raiders et al, 2020). These findings underscore the analogous molecular mechanisms of glial engulfment across species (C. elegans to human), systems (CNS/PNS), and context (development, injury, function), and they highlight the speed and precision this experimental setting affords.…”
Section: Glial Engulfment In Neural Functionmentioning
confidence: 64%
See 2 more Smart Citations
“…Some of these proteins are orthologs of molecules previously implicated in glial engulfment in Drosophila (CED-12/ELMO, CED-10/Rac1 GTPase) and mammalian retina (Rac1 GTPase) (Kevany and Palczewski, 2010;Freeman, 2015) (Table 1). In addition, we uncovered two novel mediators for glial engulfment, including a PS receptor and a regulator of PS exposure (Raiders et al, 2020). These findings underscore the analogous molecular mechanisms of glial engulfment across species (C. elegans to human), systems (CNS/PNS), and context (development, injury, function), and they highlight the speed and precision this experimental setting affords.…”
Section: Glial Engulfment In Neural Functionmentioning
confidence: 64%
“…In monitoring AMsh glia-AFD contact zones in vivo using transgenically labeled animals, we serendipitously observed labeled AFD puncta that were discontinuous with the AFD cell body and within AMsh glia. Subsequent validation studies confirmed that these puncta indeed reflect fragments of AFD ending engulfed by the AMsh glia (Raiders et al, 2020). Thus, engulfment is another glial function conserved in C. elegans.…”
Section: Glial Engulfment In Neural Functionmentioning
confidence: 73%
See 1 more Smart Citation